Oncolytic Viruses and Their Application to Cancer Immunotherapy - Chiocca, EA (Cancer Immunol Res, 2014)
Oncolytic viruses (OVs) selectively replicate in and kill cancer cells, and spread within the tumor, while not harming normal tissue. In addition to this direct oncolytic activity, OVs are also very effective at inducing immune responses to themselves and to the infected tumor cells. OVs encompass a broad diversity of DNA and RNA viruses that are naturally cancer-selective or can be genetically-engineered. OVs provide a diverse platform for immunotherapy; they act as in situ vaccines, and can be armed with immune modulatory transgenes or combined with other immunotherapies. However, the interactions of OVs with the immune system may affect therapeutic outcomes in opposing fashions: negatively by limiting virus replication and/or spread, or positively by inducing antitumor immune responses. Many aspects of the OV-tumor/host interaction are important in delineating the effectiveness of therapy; they include: (i) innate immune responses and the degree of inflammation induced, (ii) types of virus-induced cell death, (iii) inherent tumor physiology, such as infiltrating and resident immune cells, vascularity/hypoxia, lymphatics, and stromal architecture, and (iv) tumor cell phenotype, including alterations in IFN signaling, oncogenic pathways, cell surface immune markers (MHC, co-stimulatory, NK receptors), and the expression of immunosuppressive factors. Recent clinical trials with a variety of OVs, especially those expressing GM-CSF, have demonstrated efficacy and induction of antitumor immune responses in the absence of significant toxicity. Manipulating the balance between anti-virus and antitumor responses, often involving overlapping immune pathways, will be critical to the clinical success of OVs.